How controversial innovation succeeds in the periphery?: A network perspective of BASF Argentina - Glückler, Johannes (Journal of economic geography, 2014)
This article builds elements of a theory of peripheral innovation in transnational corporations. Although subsidiaries at the geographical periphery of the glob